Global stock structure of the Silky shark (Carcharhinus falciformis, Carcharhinidae) assessed with high-throughput DNA sequencing - Derek W. Kraft; Emily E. Conklin; Evan B. Freel; Melanie Hutchinson; Julia L.Y. Spaet; Robert J. Toonen; Zac H. Forsman; Michael I. Grant; John David Filmalter; John R. Hyde; Simon J.B. Gulak; Brian W. Bowen (PeerJ, 2025)
Silky shark (Carcharhinus falciformis, Carcharhinidae) numbers have declined steeply in recent decades due to the fin fishery and bycatch in pelagic fisheries. Due to a lack of data on stock delineations, this species is currently managed in ocean-spanning jurisdictions defined by regional fisheries management organizations (RFMOs). Here we investigate the global stock structure of silky sharks and compare population structure to the four RFMO boundaries. Using high-throughput sequencing from pooled individuals (pool-seq) based on 628 specimens collected opportunistically across 11 circumglobal regions, yielding 854 nuclear single nucleotide polymorphisms (SNPs) and 23 mtDNA SNPs. Results indicate significant population genetic structure between all 11 regional sampling locations, with discriminant analysis of principal components (DAPC) identifying seven discrete groups. Within the Atlantic and Indo-Pacific Oceans, FST values ranged from 0.014 to 0.035 for nuclear (nDNA) markers, and from 0.012 to 0.160 for whole mtDNA genomes, with much higher values between than within oceans (mtDNA: 0.383–0.844, nDNA: 0.042–0.078). Using an analysis of molecular variance (AMOVA) framework, 22.24% of the observed population variance is explained by RFMOs, 32.1% is explained among ocean basins, and 34.81% is explained by the DAPC-identified groups. We find significant population genetic structure within the jurisdiction of every RFMO, from which we have more than a single sampling site. Our genomic-scale results indicate discordance between population genetic structure and RFMOs, highlighting the need for a detailed study to accurately identify stock boundaries.